2006
DOI: 10.1152/ajplung.00131.2006
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine carbon particles induce apoptosis and proliferation in rat lung epithelial cells via specific signaling pathways both using EGF-R

Abstract: Apoptosis and proliferation are important causes of adverse health effects induced by inhaled ultrafine particles. The molecular mechanisms of particle cell interactions mediating these end points are therefore a major topic of current particle toxicology and molecular preventive medicine. Initial studies revealed that ultrafine particles induce apoptosis and proliferation in parallel in rat lung epithelial cells, dependent on time and dosage. With these end points, two antagonistic reactions seem to be induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 22 publications
4
79
0
Order By: Relevance
“…The elevated background after 16 h has been described earlier (5) as induced by the starving conditions under which the cells have to be kept to identify treatmentspecific reactions. Interestingly, this time course in phosphorylation has striking similarities to the time course in ERK1/2 activation that we described in our previous studies (28).…”
Section: Activation Of Akt By Npcbsupporting
confidence: 84%
See 2 more Smart Citations
“…The elevated background after 16 h has been described earlier (5) as induced by the starving conditions under which the cells have to be kept to identify treatmentspecific reactions. Interestingly, this time course in phosphorylation has striking similarities to the time course in ERK1/2 activation that we described in our previous studies (28).…”
Section: Activation Of Akt By Npcbsupporting
confidence: 84%
“…Nanoparticles have been shown to act as an extracellular stimulus that induces signaling dependent on the membrane receptors EGF-R and ␤ 1 -integrin (28). Because Akt activation was known to be initiated by these receptors on cell attachment, we investigated whether this signaling cascade is also triggered by nanoparticles.…”
Section: Activation Of Akt By Npcbmentioning
confidence: 99%
See 1 more Smart Citation
“…31 In an earlier study, Sydlik et al could show that ultrafine carbon particles activate EGFR in lung epithelial cells subsequently leading in parallel to apoptotic events as well as proliferation. 63 While the kinase activity of EGFR was found essential for both processes, β1-integrin-mediated activation of ERK was instrumental for proliferation, whereas apoptosis was mediated by activation of cJun. In other studies, it was demonstrated, that in human bronchial epithelial cells, exposure to PM2.5 particles (i.e.…”
Section: Interaction Of Nps With Cell Membrane Receptorsmentioning
confidence: 99%
“…So far, NP toxicity was mainly described through the induction of oxidative stress, inflammation and apoptosis as cellular responses. 18 Cell death highly depends on NP concentration, duration of the exposure and the cellular system investigated and both, programmed cell death (apoptosis) as well as necrosis, were observed as an outcome 63,71 . However, ROS also play important roles as intercellular second messengers and activators of specific pathways.…”
Section: The Role Of Oxidative Stress and Ros In Np Induced Signalingmentioning
confidence: 99%